2018
DOI: 10.1002/anie.201712384
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Polysubstituted Aldehydes via Visible‐Light Catalysis

Abstract: Aldehydes are among the most versatile functional groups for synthetic chemistry. However, access to polysubstituted alkyl aldehydes is very limited and requires lengthy synthetic routes that involve multiple-step functional-group conversion. This paper reports a one-step synthesis of polysubstituted aldehydes from readily available olefin substrates using visible-light photoredox catalysis. Despite a number of competing reaction pathways, commercial styrenes react with vinyl ethers selectively in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…In 2018, the same research groups showed that radical cations 58 derived from styrenes 64 can also be coupled with vinyl ethers 67 (Scheme ), thereby providing an entry to aldehydes 69 that is conceptually analogous to a previously reported α‐alkylation method for aldehydes by MacMillan and co‐workers (Scheme ) . The vinyl ethers 67 had to be used in a threefold excess to conduct the process with optimal chemoselectivity.…”
Section: Redox Neutral and Oxidative C−c π‐Bond Functionalizationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2018, the same research groups showed that radical cations 58 derived from styrenes 64 can also be coupled with vinyl ethers 67 (Scheme ), thereby providing an entry to aldehydes 69 that is conceptually analogous to a previously reported α‐alkylation method for aldehydes by MacMillan and co‐workers (Scheme ) . The vinyl ethers 67 had to be used in a threefold excess to conduct the process with optimal chemoselectivity.…”
Section: Redox Neutral and Oxidative C−c π‐Bond Functionalizationsmentioning
confidence: 98%
“…intermediate 60 ), the overall process concludes with a sulfur‐catalyzed HAT event. Given the high number of insightful reviews covering the methodological aspects of this research up to 2016, the current discussion will primarily focus on reports that appeared afterwards or that are concerned with indicative mechanistic investigations on the chalcogen co‐catalysts.…”
Section: Redox Neutral and Oxidative C−c π‐Bond Functionalizationsmentioning
confidence: 99%
“…2018 veröffentlichte dasselbe Kollaborationsteam ein Verfahren, in dem die aus den Styrolen 64 abgeleiteten Radikalionen 58 mit Vinylethern 67 umgesetzt wurden (Schema ) . Die Methode eröffnete mithin einen synthetischen Zugang zu Aldehyden 69 , der konzeptionell verwandt mit Arbeiten von MacMillan et al.…”
Section: Redoxneutrale Und Oxidative C‐c‐π‐bindungsfunktionalisierungenunclassified
“…reported an efficient and tolerant photocatalyzed synthesis of polysubstituted aldehydes with readily available styrenes and vinyl ethers by using PhSSPh as a HAT reagent [Eq. (68)] . Aldehydes with α‐, α,β‐, β,γ‐, and α,β,γ‐branches could be synthesized in good yields.…”
Section: Sulfur‐containing Hat Reagentsmentioning
confidence: 99%